THE INFLUENCE OF TAX PLANNING AND PROFITABILITY ON COMPANY VALUE WITH COMPANY SIZE AS A MODERATING VARIABLE IN CONSUMER GOODS SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FROM 2018 - 2022 - Ratih Silviyani; Galumbang Hutagalung; Wilsa Road Betterment Sitepu; Ayang Pratama (JURNAL PROFIT, 2025)
This research aims to examine the influence of tax planning and profitability on firm value, with company size serving as a moderating variable for that influence. The research data comes from 30 manufacturing companies in the consumer goods sub-sector listed on the Indonesia Stock Exchange, with a total of 150 samples taken from the years 2018 to 2022. It can be concluded from the discussion that tax planning and profitability simultaneously influence the value of the company. Unlike profitability, which affects the company's value, tax planning does not have an impact on the company's value. As a moderating element, company size can strengthen the relationship between tax planning and the company's value, as well as enhance the effect of profitability on the company's value